Analysis of Historical Learning Using the Problem-Based Learning (PBL) Model on the Entry of Hindu-Buddhist Religion in Indonesia in Class X 4 of SMA Negeri 14 Medan - Saputrinta, Yediza; Diansyah, Arfan; Gultom, Imelda (ALACRITY : Journal of Education, 2024)
The background of this research is to improve student learning outcomes through contextual and realistic problem solving at Senior High School (SMA) Problem-Based Learning makes it easier for students to develop skills in thinking and expertise in solving problems. This research is classroom action research (PTK). In this case, the subjects of this research are class X 4 students at SMA Negeri 14 Medan. The aim of this research is to gain knowledge about; 1. Planning history learning using the Problem-Based Learning model, 2. Implementation of History learning using the Problem-Based Learning model, 3. Obstacles in learning History using the Problem-Based Learning model in class X 4 SMA Negeri 14 Medan. The research method used is qualitative. The data used in this research includes primary and secondary data. Primary data was obtained from observing student and teacher activities during the learning process and the results of student learning evaluations after the learning was carried out. Meanwhile, secondary data was obtained from information regarding the number of students and facilities available to support student learning at SMA Negeri 14 Medan.